The personal library of the poet Jovaras - Narbutaitė, Gražina (Knygotyra, 1997)
One of the popular poets, Jovaras, lived in Šiauliai. He began to collect a library in 1904 when the Lithuanian press was still banned by Tsarist Russia. He had written that there were 2,000 books in his collection. However, after his death, the collection was dispersed. Jovaras never kept an inventory of his collection. Instead, he used to write the main data about the publications in it. He used a primitive classification system. Some of the books were donated with inscriptions from his friends or the authors. Some of his books (448 items) currently belong to the "Aušra" Museum in Šiauliai. The author of the article provides a detailed analysis of the books’ contents.